Effect of BaZr 0.05Ti 0.95O 3 addition on microstructure and piezoelectric properties of hydroxyapatite bone - Pisitpipathsin N. (2014)
The aim of this study was to investigate the effect of BaZr 0.05Ti 0.95O 3 (BZT) addition on the microstructure, physical, dielectric and piezoelectric properties of hydroxyapatite (HA), and develop new biomaterials which have potential applications in the support for cellular growth and in the system for bone regeneration. In this case the BaZr 0.05Ti 0.95O 3-HA composites (HABZT) were prepared by conventional sintering method. The BZT were added to HA with ratio 0, 10, 20 and 30 %wt. Then the mixed powders were pressed and subsequently sintered at the temperature ranging from 1150 to 1350°C. The result showed that the dielectric and piezoelectric properties were improved by the addition of BZT. Moreover, the bioactivity of the HA improved with addition of BZT especially at 10% as evident by the formation of bone like apatite layers on the surface of all BCZT composites after soaking in simulated body fluid (SBF) for 15 days. The results confirmed the possibility of using these bioactive composites for treatment within the human body. © (2012) Trans Tech Publications.